From dependent currency to central banking in Ceylon : an analysis of monetary experience, 1825-1957 - Gunasekera, H. A. de S. (London : London School of Economics and Political Science, University of London, 1962)
This volume describes monetary policies of the central banking in Ceylon (Sri Lanka) from 1825-1957. It examines the history of the currency and the beginning of banking in the country. This is followed by a discussion on the exchange banks, paper currency, currency boards and the beginning of central banking. The book concludes with an examination of monetary problems in an underdeveloped export economy.
A revision of the author's thesis, University of London.
Includes bibliographical references and index.
lje 24/01/2019
Loans
Keywords: Money; Central banking; Banks and banking